Metaphors in international relations theory - Marks, Michael P. (Palgrave Macmillan, 2011)
This book offers a comprehensive analysis of metaphors in theories of international relations. This book examines the metaphors that inform the major paradigms in international relations theory. Readers will discover that the vast majority of the terminology cataloguing, defining, and naming theories, concepts, and analytical tools pertaining to the study of international relations are metaphorical in nature. The book concludes that metaphors are an essential element in all aspects of international relations theory.